Hadith on the Prohibition of Music from the Perspective of Ulama Madhhab and Students of Jember - Nafiz, Farhan; Ilyas, Muhammad; Muharozak, Fahrezi (Al-Jadwa: Jurnal Studi Islam, 2025)
The law on music in Islam is an ongoing debate among Muslims, given its pervasive influence on everyday life. There are differences of opinion among ulama regarding the legal status of music, with some considering it haram while others allow it as a form of artistic expression. This study aims to detail the differences in views among ulama of Madhhab and compare them with the perspectives of students at the Kiai Haji Achmad Siddiq State Islamic University (UIN KHAS) regarding the hadith prohibiting music. The method used in this study is a qualitative approach with data collection through literature studies and interviews. The results show that students have various views: most consider music to be permissible with certain conditions, such as not containing elements of blasphemy or distancing from worship. Some students argue that music is makruh because it is considered to cause negligence, while others do not even consider there is a prohibition in the hadith, seeing it more as a matter of perspective. In addition, students emphasize the importance of the context and content of music in determining its status. This study is expected to clarify students’ understanding of the hadith prohibiting music, show its relevance in modern life, and encourage a more open discussion between tradition and developments.